Guiana Dolphin (Sotalia guianensis) in the Maracaibo Lake System, Venezuela: Conservation, Threats, and Population Overview - Barrios-Garrido, Hector; De Turris-Morales, Kareen; Espinoza-Rodriguez, Ninive Edilia (Frontiers in Marine Science, 2021)
The Guiana dolphin (Sotalia guianensis) home range is located among Central and South American countries, in coastal habitats in the Caribbean and Atlantic Ocean. Its distribution is scattered, with multiple population centres which are under threats that vary based on local realities. We compiled and assessed biological data from multiple sources (published and unpublished data) to improve our understanding regarding the Maracaibo Lake Management Unit, which is an isolated and unique population core of this species. We identified at least two distinguishable population centres throughout the Maracaibo Lake System, one in the northern portion – in the Gulf of Venezuela, and another in the southern portion of the Maracaibo Lake itself. Both centres have differences in some biological aspects (e.g. group size and habitat use), but similarities in the human-induced pressures (e.g. intentional take, habitat degradation, and traditional use). We detailed the uses of Guiana dolphin (consumptive and non-consumptive) by community members, including the use as talismans for indigenous fishers and consumption of its meat as a religious belief (Easter period), and dolphin watching tours carried out by local companies. In one artisanal port, at least 15 animas are intentionally taken annually to be used for local consumption, shark-bait, or trade; however, we acknowledge that this annual take is likely an underestimate. Further research is needed to clarify how and at what magnitude mentioned and other key-threats are impacting over Guiana dolphin MU in the Maracaibo Lake System.